Low-dose CT angiography of the abdominal aorta and reduced contrast medium volume: Assessment of image quality and radiation dose. Issue 1 (January 2016) - Nijhof, W.H.; Baltussen, E.J.M.; Kant, I.M.J.; Jager, G.J.; Slump, C.H.; Rutten, M.J.C.M.
Abstract : Aim: To determine the effect of using 80 kV tube voltage and a reduced amount of contrast medium on the image quality and radiation dose of computed tomography angiography (CTA) of the abdominal aorta. Materials and methods: Patients who were referred for a CTA examination of the abdominal aorta were included in this technical efficacy study. Thirty patients were divided randomly into two groups. Fifteen patients underwent a dual-energy CT (DECT) protocol (Group A). Fifteen patients were scanned with the use of an automated tube potential selection algorithm tool (Group B). In both protocols, a test bolus injection of 10 ml ioversol (350 mg iodine/ml) was used, followed by 20 ml of 1:1 saline-diluted contrast medium. Quantitative analysis comprised determination of the mean attenuation and contrast-to-noise ratio. Qualitative image analysis was performed independently by five radiologists. The estimated radiation dose in terms of CT dose index and effective dose was recorded and compared with a standard 120 kV protocol. Results: In Group B, six patients underwent CTA at 80 kV, seven patients underwent CTA at 100 kV and two patients underwent CTA at 120 kV. The mean contrast-enhancement values of Group A (80 kV) and the 80 kV subgroup of Group B were 16.5% and 27.6% higher compared to the 100 kV subgroup of Group B, these differences were, however, not significant. There were no significant differences in mean image quality between groups. In patients undergoing CTA at 80 kV the effective dose decreased by up to 51.3% compared to a conventional 120 kV CTA protocol. Conclusions: The findings of this study support the hypothesis that 80 kV in CTA of the abdominal aorta can reliably be used with only 30 ml contrast medium in total and a 50% reduction in radiation dose. The overall image quality was diagnostically adequate; however, it appeared to be suboptimal in patients with a BMI above 28 kg/m 2 . Highlights: Lowering the tube voltage permits the use of reduced amount of iodinated contrast medium. Lowering the tube voltage does not compromise the overall image quality. Lowering the total amount of contrast medium to a total of 30 mL appeared to be suboptimal in patients with a BMI above 28 kg/m 2 . Lowering the tube voltage reduced the effective dose with up to 51.3%.